IMPLEMENTASI PROGRAM FULL DAY SCHOOL DALAM MENGEMBANGKAN KARAKTER RELIGIUS DAN PRESTASI AKADEMIK SISWA - Sari, Intan Dwi Kurnia; Hikmawati, Ari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study originates from the need of madrasahs to connect academic learning with the development of religious character through the implementation of a full day school program, which has thus far been rarely examined in public Islamic schools. This research aims to describe the planning, implementation, and outcomes of the full day school program in cultivating students’ religious character and improving their academic achievement at MTs Negeri 2 Karanganyar in the 2025/2026 academic year. A qualitative approach was applied using a field research design with data collected through observation, interviews, and documentation involving the principal, Islamic education teachers, the vice principal for student affairs, and students. The findings show that the program was designed through the preparation of an integrated schedule and collaborative task distribution, and was implemented through a series of academic and religious activities carried out throughout the day. The main results indicate an improvement in students’ worship discipline, religious participation, and academic scores in several core subjects, accompanied by challenges such as student fatigue and limited facilities. Overall, the full day school program contributes positively to the integration of learning and character education and serves as a reference for development in public madrasahs seeking to strengthen religious habituation within the school environment. ABSTRAK Penelitian ini berangkat dari kebutuhan madrasah untuk menghubungkan pembelajaran akademik dengan pembentukan karakter religius melalui penerapan program full day school yang hingga kini masih jarang dikaji pada madrasah negeri. Penelitian ini bertujuan mendeskripsikan perencanaan, pelaksanaan, dan capaian program full day school dalam membangun karakter religius dan meningkatkan prestasi akademik siswa di MTs Negeri 2 Karanganyar Tahun Ajaran 2025/2026. Pendekatan kualitatif digunakan melalui desain penelitian lapangan dengan teknik observasi, wawancara, dan dokumentasi yang melibatkan kepala sekolah, guru PAI, wakil kepala sekolah bidang kesiswaan, dan siswa. Hasil penelitian menunjukkan bahwa program dirancang melalui penyusunan jadwal terpadu dan pembagian tugas yang kolaboratif, kemudian dijalankan dalam rangkaian aktivitas akademik dan religius yang berlangsung sepanjang hari. Temuan utama memperlihatkan peningkatan kedisiplinan ibadah, partisipasi religius siswa, serta kenaikan nilai akademik pada beberapa mata pelajaran inti, disertai kendala berupa kelelahan siswa dan keterbatasan sarana. Secara keseluruhan, program full day school memberikan kontribusi positif terhadap integrasi pembelajaran dan pendidikan karakter, serta menjadi rujukan pengembangan bagi madrasah negeri dalam memperkuat pembiasaan religius di lingkungan sekolah.